Increase Results Student Learning Through Model Interactive Learning Based on Lesson Antivity Citizenship - Anggita, Dian Giska (Journal of Elementary School Education, 2025)
Importance of interaction in the Civics Education (PKn) learning process to achieve more effective learning goals. In this study, a literature review method is used to collect and analyze previous research results. process teach teacher become cast main in create situationeducational interactive, namely interaction between teacher and students , students with student and with source learning in support achieved objective study. The research findings indicate that the use of interactive activity-based learning models can improve the learning achievement of sixth-grade students in the Civics subject. The method I use is the literature method riview. This method is a systematic way to collect, rotate and synthesize existing works of research and practitioner thought. This method allows students to be more active in learning, especially through question-and-answer sessions, discussions, and creative dialogues. Thus, it can be concluded that the interactive activity- based learning model is effective in improving student learning outcomes in the civics subject.